Phytophthora ramorum and Phytophthora kernoviae on naturally infected asymptomatic foliage - Denman, S.; Kirk, S. A.; Moralejo, E.; Webber, J. F. (EPPO Bulletin, 2009)
Phytophthora ramorum and Phytophthora kernoviae are recently discovered invasive Phytophthoras causing leaf necrosis and shoot tip dieback mostly on ornamental and forest understorey species, but also cause bleeding cankers on stems of a wide range of tree species. Sporulation occurs only on infected shoots or fruits and foliage so foliar hosts are central to the disease epidemiology. In field trials to assess infection in trap plants exposed to natural inoculum of P. ramorum and P. kernoviae on rhododendron in south west England, it was discovered that leaves of the trap plants (Rhododendron‘Cunninghams White’) and holm oak (Quercus ilex) were asymptomatically infected and supported sporulation of both pathogens. More than half the rhododendron trap plants exposed to inoculum of P. kernoviae became infected compared with approximately a third of those exposed to P. ramorum in a natural situation. Approximately one third of the infections were detected from asymptomatic foliage for both pathogens. The significance of these findings for plant health regulation based on visual inspection as a measure to prevent introduction and dissemination of both these pathogens is explored and research gaps identified.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: asymptomatic infection; pathogen sporulation (voyant); Phytophthora kernoviae; Phytophthora ramorum